2019
DOI: 10.1016/j.ebiom.2019.05.044
|View full text |Cite
|
Sign up to set email alerts
|

A targeted proteomics approach reveals a serum protein signature as diagnostic biomarker for resectable gastric cancer

Abstract: Background Gastric cancer (GC) is the third leading cause of cancer death. Early detection is a key factor to reduce its mortality. Methods We retrospectively collected pre- and postoperative serum samples as well as tumour tissues and adjacent normal tissues from 100 GC patients. Serum samples from non-cancerous patients were served as controls ( n = 50). A high-throughput protein detection technology, multiplex proximity extension assays (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…The small normal sample size may lead to some bias in the results. Other omics fields, such as genome, transcriptome, proteome, and metabolome, have shown respective advantages in GC diagnostic and prognostic models ( Li et al, 2010 ; Chan et al, 2016 ; Deng et al, 2018 ; Zhang et al, 2018 ; Shen et al, 2019 ); therefore, it is too early to assert that our model is optimal. The models should be validated in a real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The small normal sample size may lead to some bias in the results. Other omics fields, such as genome, transcriptome, proteome, and metabolome, have shown respective advantages in GC diagnostic and prognostic models ( Li et al, 2010 ; Chan et al, 2016 ; Deng et al, 2018 ; Zhang et al, 2018 ; Shen et al, 2019 ); therefore, it is too early to assert that our model is optimal. The models should be validated in a real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
“…APBB1IP integrates signaling events that are critical for integrin-mediated immune function control and cancer progression (Patsoukis et al, 2019 ). Some studies have shown that APBB1IP is a new biological marker associated with gastric cancer and head and neck squamous cell carcinoma (Sanati et al, 2018 ; Shen et al, 2019 ). The Niemann–Pick type C2 (NPC2) protein is involved in the regulation of intracellular cholesterol homeostasis via direct binding with free cholesterol (Kamata et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rPSL SWATH allowed the identification of well-documented and clinically significant (supported by the literature) plasma proteins. Numerous studies have proposed CEA as a late-stage CRC biomarker (35), as well as for lung (36) and gastric cancers (37). Plasma IL6, CXCL8 and ILB1 have been also proposed as diagnostic markers in CRC, brain, breast, oral and prostate cancers (45–47, 5557).…”
Section: Discussionmentioning
confidence: 99%